Intended. Underrated. Disputed. The IOC Medical Commission's "Subcommission on Doping and Biochemistry in Sport" between 1980 and 1988. Issue 3 (June 2016) - Krieger, Jörg
Abstract: Based on historical sources from the archive of the International Olympic Committee Library and Archives and the Carl and Liselott Diem-Archive of the German Sport University Cologne, this article explores the role of the International Olympic Committee Medical Subcomission on Doping. It therewith aims to address the relative omission on the role of scientists in the history of anti-doping. The paper argues that the IOC MSD is a much-underrated anti-doping body because the activities of its members, who were all heads of anti-doping laboratories with professional competencies in the field of doping analysis, shaped the International Olympic Committeés (IOC) anti-doping policy considerably in the 1980s.